Meningkatkan Hasil Belajar Melalui Pembelajaran Kooperatif Tipe Ngroup To Group Exchange (NTGE) pada Mata Pelajaran Fikih bagi Siswa MTs. Al-Ikhlas Mentigi - Haulid Haulid (Universitas Pendidikan Mandalika, 2020)
This study aims to determine the increase in learning outcomes through cooperative learning type Ngroup To Group Exchange (NTGE) in the Fiqih subject for students class VII MTs. Al-Ikhlas Mentigi. This research uses Classroom Action Research with the subjects of students class VII MTs. Al-ikhlas Mentigi with a total of 20 people. The research instrument used learning outcomes tests to obtain quantitative data and observation sheets to obtain qualitative data. The collected data were analyzed using quantitative and qualitative descriptive analysis. The results of this study indicate that the increase in student learning outcomes with the results of the initial reflection before the implementation of the action with an average in the first cycle can be said to be insufficient or still lacking, namely 68.62 then increased in the second cycle by 80.03. So it can be concluded that; (1) The application of the Ngroup To Group Exchange (NTGE) type of learning model is one of the best choices in motivating students' interest. (2) The application of the NTGE type learning model makes learning directed and innovative. (3) The application of the NTGE type learning model can improve student learning outcomes so that it shows changes in student attitudes to be more caring and creative about the learning atmosphere.